Review of learning management systems: history, types, advantages, and challenges - Fahad Taha Al-Dhief; Ali Al Nasser; Shafazawana Mohamed Tharikh; Hassan Al Nasser; Ali Abdul Ghaffar Al-Mosleh; Musatafa Abbas Abbood Albadr; Majid Razaq Mohamed Alsemawi (Institute of Advanced Engineering and Science, 2024)
As technological advancements continue in the higher education domain, the systems of higher learning management in universities and institutions have witnessed significant attention from researchers and developers. The technologies of these systems can present extremely useful tools and provide many advantages to enhance learning and increase the students’ performance. However, there are some issues and challenges that face these systems and need to be highlighted. Moreover, there is a need to review the advantages of such systems in order to motivate other countries to adopt, use, and develop the learning systems. Therefore, this paper gives an overview of the learning management systems (LMSs) in universities and institutes. Furthermore, it presents the history of LMSs, usages, systems types, advantages, challenges and issues.